Granulocyte-Macrophage Colony-Stimulating Factor Modulates Myeloid-Derived Suppressor Cells and Treg Activity in Decompensated Cirrhotic Patients With Sepsis - Sehgal, Rashi; Maiwall, Rakhi; Rajan, Vijayaraghavan; Islam, Mojahidul; Baweja, Sukriti; Kaur, Navkiran; Kumar, Guresh; Ramakrishna, Gayatri; Sarin, Shiv K.; Trehanpati, Nirupma (Frontiers in Immunology, 2022)
Background Decompensated cirrhosis patients are more prone to bacterial infections. Myeloid-derived suppressor cells (MDSCs) expand in sepsis patients and disrupt immune cell functions. Granulocyte-macrophage colony-stimulating factor (GM-CSF) therapy helps in restoring immune cell functions and resolving infections. Its role in MDSC modulation in cirrhosis with sepsis is not well understood. Methods A total of 164 decompensated cirrhotic—62 without (w/o), 72 with sepsis, and 30 with sepsis treated with GM-CSF—and 15 healthy were studied. High-dimensional flow cytometry was performed to analyze MDSCs, monocytes, neutrophils, CD4 T cells, and Tregs at admission and on days 3 and day 7. Ex vivo co-cultured MDSCs with T cells were assessed for proliferation and apoptosis of T cells and differentiation to Tregs. Plasma factors and mRNA levels were analyzed by cytokine-bead assay and qRT-PCR. Results Frequencies of MDSCs and Tregs were significantly increased (p = 0.011 and p = 0.02) with decreased CD4 T cells (p = 0.01) in sepsis than w/o sepsis and healthy controls (HCs) (p = 0.000, p = 0.07, and p = 0.01) at day 0 and day 7. In sepsis patients, MDSCs had increased IL-10, Arg1, and iNOS mRNA levels (p = 0.016, p = 0.043, and p = 0.045). Ex vivo co-cultured MDSCs with T cells drove T-cell apoptosis (p = 0.03, p = 0.03) with decreased T-cell proliferation and enhanced FOXP3+ expression (p = 0.044 and p = 0.043) in sepsis compared to w/o sepsis at day 0. Moreover, blocking the MDSCs with inhibitors suppressed FOXP3 expression. GM-CSF treatment in sepsis patients significantly decreased MDSCs and FOXP3+ Tregs but increased CD4 T-cell functionality and improved survival. Conclusion MDSCs have an immunosuppressive function by expanding FOXP3+ Tregs and inhibiting CD4+ T-cell proliferation in sepsis. GM-CSF treatment suppressed MDSCs, improved T-cell functionality, and reduced Tregs in circulation.